THE EFFECT OF USING “EDMODO AND QUIPPER SCHOOL” IN BLENDED LEARNING METHOD TOWARDS STUDENTS’ WRITING SKILL AT THE SECOND YEAR STUDENTS OF SMAN 1 BENGKULU TENGAH - Dian Permatasari (JOALL (Journal of Applied Linguistics and Literature), 2018)
This research aims to compare whether there was an effect on students’ writing quality when students were taught with blended learning method, combined with Edmodo or Quipper School. This was a quasi-experimental research with 72 students at grade XI MIPA SMAN I Bengkulu Tengah, Indonesia as the samples. The experiment group was taught with Edmodo while the control group was taught with Quipper School. The instrument was a writing test. The findings of this research, with respect to the comparison of post test mean scores between the experimental group and the control group, were as follows. There was a significant difference on students’ general writing ability. There were significant differences on students’ writing ability in the aspects of content and language use. However, there was no significant difference.The students’ responses were positive toward the use of Edmodo as a blended learning. Further studies are recommended for other school levels. It seems that Edmodo is more effective than Quipper School in writing lesson since the learning platform in Edmodo gives facilities for the students to work independently, enables them to improve their quality and has more practical, interactive, and interesting features.